1993
DOI: 10.1002/1097-4679(199301)49:1<3::aid-jclp2270490102>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Emotional experiences during the three trimesters of pregnancy

Abstract: This study examined the emotional changes that occur during the trimesters of pregnancy. Two hundred eighty‐two women were asked, one day after giving birth, to indicate at what frequency they had experienced various symptoms during each trimester of pregnancy and to fill out the Repression Sensitization scale (Byrne, Barry, & Nelson, 1963). Results showed that while women's feelings during the first trimester are characterized by symptoms related to physiological changes (e.g., nausea, vomiting, dizziness), d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 25 publications
1
35
0
6
Order By: Relevance
“…While minor discomforts are common across pregnancy [36] [37], around 36% of all women (39% in nulliparous) in the current study reported experiencing moderate or extreme levels of pain during pregnancy. The experience of moderate or extreme pain and/or discomfort was associated with childbirth fear.…”
Section: Discussionmentioning
confidence: 99%
“…While minor discomforts are common across pregnancy [36] [37], around 36% of all women (39% in nulliparous) in the current study reported experiencing moderate or extreme levels of pain during pregnancy. The experience of moderate or extreme pain and/or discomfort was associated with childbirth fear.…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal depression had been identified as a risk factor for PND [Jossefson et al, 2001;Larsson et al, 2004], adverse obstetrical and neonatal outcomes [Chung et al, 2001], and growth retardation in infants [Zukerman et al, 1989]. Because studies have shown that depression is more common late in the pregnancy [Bennet et al, 2004;Kumar and Robson, 1984;Rofe et al, 1993], and most pregnant women in Africa schedule delivery late in the second or the third trimester, assessing for depression in late pregnancy is appropriate for detecting women in need of intervention to safeguard maternal and family psychosocial well-being.…”
Section: Introductionmentioning
confidence: 99%
“…This arises from the fact that various changes in skin, genital, urinary and gastrointestinal tract may also affect the BIP, apart from the changes of BMI observed during pregnancy. Changes in self-esteem levels in pregnancy may be impacted by several factors such as the level of education, maternal age, number of previous births, duration of marriage, the income level of the family, regardless of a planned pregnancy (27)(28)(29)(30)(31). Therefore, in our study, the patients with similar demographic, social and medical characteristics were compared in terms of self-esteem and BIP.…”
Section: Discussionmentioning
confidence: 99%